2023
DOI: 10.18502/ijm.v15i1.11914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation PCR panel of the FilmArray® pneumonia plus for pathogen detection of ventilator-associated pneumonia in children and its impact on therapeutic management

Abstract: Background and Objectives: Ventilator-associated pneumonia (VAP) is the second most common nosocomial infection in pediatric intensive care units. The aim of this study was to evaluate the contribution of multiplex PCR in the diagnosis of VAP and its impact on the clinical and prognostic outcome of children in the ICU. Materials and Methods: This is a prospective observational study from March to November 2021, including bronchial samples collected from 38 intubated children hospitalized in ICU. The dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Out of the 33 patients diagnosed with VAP, more than half (65.9%) had multiple pathogens detected; K. pneumonia P. aeruginosa, and Acinetobacter calcoaceticus-baumannii complex were the most frequently isolated pathogens. There is only one prospective observational study about the evaluation of the FA-PP in children with VAP in the PICU [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the 33 patients diagnosed with VAP, more than half (65.9%) had multiple pathogens detected; K. pneumonia P. aeruginosa, and Acinetobacter calcoaceticus-baumannii complex were the most frequently isolated pathogens. There is only one prospective observational study about the evaluation of the FA-PP in children with VAP in the PICU [17].…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed a PPA of 97%, with a negative NPA agreement of 95% compared to normal antibiotic sensitivity testing. Debbagh et al [17] demonstrated that the identification of resistance genes revealed a significant prevalence of carbapenemases (65.2%) and ESBLs (34.8%) using the FA-PP in a pediatric setting. This observation can be attributed to the administration of previous, frequently broad-spectrum, antibiotic treatment among critically ill patients admitted to the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional study confirms the greater incidence of viruses in NP among children. Debbagh and co-workers conducted a small, single-centre analysis of pediatric VAP, which explored viral etiologies in 38 children [ 20 ]. Extensive testing of bronchial secretions with mPCR demonstrated the presence of a virus in the lower airway in 30.7% of patients [ 20 ].…”
Section: Pediatric Viral Npmentioning
confidence: 99%